Family Violence Against Women: Analysis From a Personalist Approach - Caqui Pajuelo, Yolanda Maricruz (2020)
In 2013, the World Health Organization affirmed that one in three women in the world suffers physical and / or sexual violence by their partner, reflecting with this statement the seriousness of family violence in the world. Unfortunately, women subjected to this scourge are twice as prone to experiencing mental illness and abuse in the consumption of alcohol and drugs, unlike those who have not suffered from family violence. Statistics also indicate that 42% of women who have experienced physical and sexual violence by their partners are prone to serious injuries and even death from it. Violence against women denotes a serious global health problem, significantly affects both the mental, physical and spiritual health of women whose dignity is violated and must be fought by focusing on the person in an integral way, as maintained by Personalism. According to the reality expressed, the purpose of this research is to explain from a personal approach the anthropological foundations of the dignity of women, recognizing the intrinsic value that it possesses, the same that is violated in a context of family violence.